PENGARUH CR, DER DAN ROA TERHADAP DIVIDEND PAYOUT RATIO PADA BEBERAPA PERUSAHAAN PERTAMBANGAN yang Terdaftar di BEI (2011-2013) - Halim Usman; Sri Wahyuni Mustafa (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2014)
This research is motivated by previous research fieldwork-examine some of the variables that affect the dividend payout ratio as the dependent variable, both in Indonesia and abroad. This study used a sample of three mining companies listed on the Stock Exchange. The dependent variable in this study is the Dividend Payout Ratio (DPR) while the independent variable is Cash Ratio (CR), Debt to Equity Ratio (DER) and Return on Assets (ROA) and used multiple regression analysis to determine the effect of independent variables on the dependent variable. The results showed that CR, DER and ROA of 25.60% influence Parliament and the balance of 74.40% is influenced by other variables not included in this study.